Architectures of knowledge : firms, capabilities, and communities / Ash Amin and Patrick Cohendet. - Amin, Ash (Oxford University Press, 2003)
'Architectures of Knowledge' demonstrates that a recognition of the importance of the role of knowledge in economics may lead to a new conception of the firm or business enterprise, and public policy.